Youth protest and the 2014 national elections: The case of Zamdela Sasolberg - Rampedi, Mahlatse (Electoral Institute for Sustainable Democracy in Africa, 2017)
There is a general perception that youth are apathetic to local politics and national elections. At the same time, young people are often at the forefront of protest. Both electoral politics and protest are forms of political participation; however, the relationship between the two is under-explored. In Zamdela, young people were politicised by two events: the January 2013 protest, and the formation of the Economic Freedom Fighters (EFF) in mid-2014. In addition, many youth are simply conflicted by the lack of service delivery by the ruling party and the lack of viable alternatives in elections. Using qualitative data, this article traces and thematically analyses the political attitudes of youth in Zamdela between the demarcation protest of January 2013 and the May 2014 national elections. Quantitatively, the article provides practical data describing the way in which young people engaged with the 2014 national elections, given the fluctuating perspectives throughout 2013 and 2014. Against this background the article analyses the notion of youth apathy towards politics and elections, as well as Booysen’s (2007) ‘ballot and the brick’ analysis of political engagement, protest and elections. The article demonstrates that a high proportion of young people are politically aware, participated in the protest, voted in elections, and evinced an increased likelihood of voting for parties other than the ANC.
Keywords: Youth - South Africa - Political activity; Political participation - South Africa; South Africa - Politics and government - 21st century; Elections - South Africa; African National Congress; Economic Freedom Fighters